Usabilitas Twitter, Facebook, Youtube, dan Tiktok - Munadhil Abdul Muqsith (ADALAH, 2022)
New media technologies Twitter, Facebook, YouTube, and TikTok are on the way to Reusability. To meet user satisfaction, each online media network vendor is competing to create a website platform to have unique advantages and differences in the virtual world market by increasing its usability. For that, let's discuss what is meant by Usability and its theory.